Facilitating Trade and Structural Adjustment Chile Experiences in Non-Member Economies - Bartók, Csilla (OECD Trade Policy Papers, 2007)
This paper is the first of four country case studies which is a part of a broader research programme addressing trade and structural adjustment issues in non-member economies which was conducted as a follow-up to Trade and Structural Adjustment: Embracing Globalisation (OECD, 2005) which identified policies for successful trade-related structural adjustment. This paper studies the trade liberalisation experience of Chile from 1973 onward. The report consists of 5 main parts; Part 1 provides the introduction, part 2 looks at the trade liberalisation in Chile which was implemented in three phases, (1) initial trade reforms (1973-84), (2) trade reform after a temporary policy reversal(1985-89) and (3) after 1990. Part 3 looks at the evolution and structure of exports and imports, and Part 4 looks at sectoral developments in the copper industry, agrofood industry, wood and wooden products industry and the textiles and clothing industry. Part 5 concludes with lessons learnt. The experience of Chile shows that trade reform has been essential for realigning the incentive structures in Chile. A stable macroeconomic environment, trade reform starting with the elimination of quantitative restrictions, introduction of flat tariffs, coherent exchange rate policy, sound institutional framework, rule of law, mild promotion of exports, use of foreign capital, and relatively flexible labour market policies have been important factors in Chili's successful trade liberalisation experience